2011
DOI: 10.1890/10-2240.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and quality: unifying food web and ecosystem perspectives on the role of resource subsidies in freshwaters

Abstract: Although the study of resource subsidies has emerged as a key topic in both ecosystem and food web ecology, the dialogue over their role has been limited by separate approaches that emphasize either subsidy quantity or quality. Considering quantity and quality together may provide a simple, but previously unexplored, framework for identifying the mechanisms that govern the importance of subsidies for recipient food webs and ecosystems. Using a literature review of > 90 studies of open-water metabolism in lakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
377
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(398 citation statements)
references
References 81 publications
16
377
2
3
Order By: Relevance
“…Affected ecosystems may extend beyond areas adjacent to invaded ecosystems and be hundreds of kilometers away depending on the behavior of the animals that connect them (Reiners and Driese 2004), such as salmon (Holtgrieve and Schindler 2011). Despite an abundance of literature demonstrating that resources from one ecosystem can affect another, few subsidy studies have integrated an ecosystem-level approach (Marcarelli et al 2011). Movement of animals can represent large nutrient fluxes between habitats, such as through regular or periodic movements (Meyer et al 1983, Post et al 1998, Gende et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Affected ecosystems may extend beyond areas adjacent to invaded ecosystems and be hundreds of kilometers away depending on the behavior of the animals that connect them (Reiners and Driese 2004), such as salmon (Holtgrieve and Schindler 2011). Despite an abundance of literature demonstrating that resources from one ecosystem can affect another, few subsidy studies have integrated an ecosystem-level approach (Marcarelli et al 2011). Movement of animals can represent large nutrient fluxes between habitats, such as through regular or periodic movements (Meyer et al 1983, Post et al 1998, Gende et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Externally derived nutrients can influence the productivity and structure of ecosystems ranging from oceanic islands to freshwater ecosystems (Stapp and Polis 2003, Anderson et al 2008, Moore et al 2008, Richardson et al 2009, Wipfli and Baxter 2010. However, responses vary depending on the nature of a subsidy, the physical characteristics of donor and recipient systems, and the mechanisms or capacities of connectivity between them (Yang et al 2008, Hocking and Reynolds 2011, Marcarelli et al 2011. Nutrient subsidies can further be mediated by the traits of individuals or species in recipient habitats such as mobility, spatial distribution, phenology, feeding ecology and body size (Polis et al 1997, Anderson et al 2008, Hocking et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…While freshwater ecosystems are known to be supported by both terrestrial-and locally derived resources (Post 2002, Thorp and Delong 2002, Marcarelli et al 2011, there is conflicting research on the importance of terrestrial-derived subsidies in estuarine productivity. We found much stronger effects of terrestrial resources than some studies (Deegan and Garritt 1997, Chanton and Lewis 1999, 2002.…”
mentioning
confidence: 99%
“…These included questions of duration and magnitude (e.g., Yang et al 2008), resource quality (size, nutritional value, protective chemicals, etc. ; e.g., Marcarelli et al 2011), influence on intensity of trophic cascades, and impacts on recipient system stability. The final question was about quantitative predictions, the subject of this special issue of the Canadian Journal of Fisheries and Aquatic Sciences.…”
Section: Alternate Trajectories Of Consumer Population Responses To Smentioning
confidence: 99%
“…Changes in the quality and quantity of subsidies to streams of leaves and terrestrial invertebrates due to shifts in riparian species composition have been shown (e.g., Wipfli 1997;Marcarelli et al 2011). Roon et al (2016, this issue) provide another example of how non-native species of riparian trees can alter the quantity (and perhaps timing) of terrestrial invertebrate inputs.…”
Section: Special Issuementioning
confidence: 99%